Left Ventricular Dimension after Mitral Valve Surgery in Rheumatic Mitral Stenosis: the Impact of Myocardial Fibrosis - Teuku Muhammad Haykal Putra; Renan Sukmawan; Dwita Rian Desandri; Celly Atmadikoesoemah; Elen Elen; Manoefris Kasim (Journal of Tehran University Heart Center, 2020)
Background: Patients with rheumatic mitral stenosis (MS) experience changes in left ventricular (LV) dimensions after mitral valve surgery. We sought to investigate changes in LV dimensional parameters after mitral valve surgery and find out whether the same changes occurred in different extents of myocardial fibrosis.